2014
DOI: 10.3748/wjg.v20.i38.14040
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of early detection of colorectal tumours by stool methylation markers: A meta-analysis

Abstract: Stool-based DNA testing may be useful for noninvasively diagnosing colorectal tumours and SFRP2 methylation is a promising marker that has great potential in early CRC diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Zhang et al 69 evaluated the accuracy of gene methylation analysis of DNA in stool samples for diagnosing CRC. They included 37 articles that comprised 4484 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 69 evaluated the accuracy of gene methylation analysis of DNA in stool samples for diagnosing CRC. They included 37 articles that comprised 4484 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic meta-analysis has revealed that the pooled sensitivity and specificity of methylated SFRP2 are 0.71 and 0.94, respectively 41 . SFRP2 methylation is therefore a promising biomarker for CRC screen 42 . The DNA stool test of SFRP1hypermethylation also achieves a sensitivity of 89% and specificity of 86% in colorectal neoplasia detection 35 .…”
Section: Multiple Dna Methylation Biomarkersmentioning
confidence: 99%
“…La letteratura riporta pochi report-studi che attribuiscono al test una sensibilità vicina al 90-100%, mentre numerosi lavori indicano valori più bassi non superiori al 50% [46].…”
Section: Raccomandazioni Per Lo Screeningunclassified